1995
DOI: 10.1159/000196392
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Cholesterol in Differentiating Transudates and Exudates

Abstract: Two hundred and four patients with pleural effusion were studied to investigate the utility of Light’s criteria and pleural fluid cholesterol level (pCHOL) in the identification of exudative pleural effusion (EPE) and transudative pleural effusion (TPE). There were 48 TPE, 56 tumor, 47 tuberculous, 30 metapneumonic and 23 miscellaneous patients. A value ≧ 54 mg/dl for pCHOL and > 0.32 for the pleura/serum cholesterol ratio (p/sCHOL) showed sensitivity (S) and specificity (Sp) of 95.5% and 91.6% for pCHOL, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The cause of the elevated concentration of CHOL in pleural exudates is not clear. Various possible explanations have been reported [11, 13, 19]. The hypothesis that the increase in pleural CHOL in exudates may result from a greater capillary permeability since there is a correlation between pleural CHOL and serum CHOL seems to be more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of the elevated concentration of CHOL in pleural exudates is not clear. Various possible explanations have been reported [11, 13, 19]. The hypothesis that the increase in pleural CHOL in exudates may result from a greater capillary permeability since there is a correlation between pleural CHOL and serum CHOL seems to be more likely.…”
Section: Discussionmentioning
confidence: 99%
“…This method may correctly classify up to 99% of pleural effusions as exudates or transudates. However, other authors found poorer diagnostic results when applying these criteria [9, 10, 11]. Several tumor markers and biochemical parameters have been proposed in an effort to improve the differential diagnosis of pleural effusion [12, 13, 14, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Pleural fluid develops in the pleural space through different mechanisms [1, 2, 3, 4]. An important step of its evaluation is the distinction between transudates and exudates.…”
Section: Discussionmentioning
confidence: 99%
“…Exudative pleural effusions are the consequence of local inflammation which affects the permeability of pleural surfaces or the lymphatic drainage in the location where the fluid originates [1, 2]. Pleural transudates are due to diseases modifying the plasma colloid-osmotic pressure in pleural capillaries, or to several systemic factors affecting the hydrostatic pressure and alter the mechanism of formation or absorption of pleural fluid [1, 2, 3]; pleural fluid may even be formed by the passage of peritoneal fluid into the pleural space [4]. The criteria proposed by Light et al [5]discriminate pleural exudates on the basis of a pleural fluid to serum protein ratio >0.5 and/or a pleural to serum lactate dehydrogenase (LDH) ratio >0.6.…”
Section: Introductionmentioning
confidence: 99%
“…Other exudate/transudate studies have looked at the use of pleural fluid cholesterol (9), albumin gradient (10) and serum/fluid bilirubin ratio (11); however, these have been shown to be less accurate than Light’s criteria (12). The weakness of Light’s criteria is that approximately 20% of heart failure‐related effusions in patients taking diuretic therapy are identified as exudates (13).…”
Section: Investigation – Pleural Fluidmentioning
confidence: 99%